2014
DOI: 10.2478/s11756-014-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Amsonia orientalis

Abstract: Amsonia orientalis Decne. (Apocynaceae), is a rare and threatened plant species which is located only in a constricted area in northeast of Greece and northwest of Turkey in the world. Although phylogenetic analysis depending on nucleotide sequences of genes from different sources (nucleus, mitochondria and chloroplast) became a major tool for classification of plant species, there is still a big lack of information about A. orientalis in the international molecular data bases such as NCBI. In the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The number of these individuals was increased through an in vitro propagation study (1). To determine the genetic consistency among these populations in Balıkesir province, Gürkanlı et al (14) conducted a detailed genetic study, and genetic variation was found between the four different populations. Therefore, only individuals from the Gaziosmanpaşa population were propagated and employed in this study to ensure genetic stability and homogeneity among plantlets.…”
Section: Methodsmentioning
confidence: 99%
“…The number of these individuals was increased through an in vitro propagation study (1). To determine the genetic consistency among these populations in Balıkesir province, Gürkanlı et al (14) conducted a detailed genetic study, and genetic variation was found between the four different populations. Therefore, only individuals from the Gaziosmanpaşa population were propagated and employed in this study to ensure genetic stability and homogeneity among plantlets.…”
Section: Methodsmentioning
confidence: 99%